Towards the development of public accessed portal : a case study of understanding a direct selling business model in Malaysia / Fitri Mohamad Sinan - Mohamad Sinan, Fitri (Faculty of Computer and Mathematical Sciences, 2006)
Direct Selling already known as a door^to^door business that selling products directly to the customers. This type of business does not require fixed places to practice the business. Usually, the products that sell by direct seller cannot be found in regular market such as in supermarket or hypermaricet. And also, the products that sells by direct sales company is an exclusive goods that quite difficult to sell in regular market such as cosmetics, supplementary foods and much more. The government always monitors the products that provided by direct sales company to ensure it is safe to use by consumers. Direct selling can be categorized into 3 categories, which are Multi-level Marketing (MLM), SingleJevel Marketing (SLM) and Mail Order (MO). Right now, most of the public does not understand what direct selling is and what are their rights. This is because of lack of information regarding direct selling activities. There are no standard portals that can be access by public to know and understand what is direct selling and how the business model looks like. The only option is by referring to the Ministry of Domestic Trade and Consumer Affairs (MDTCA) website. The weaknesses to this website are the public cannot interact with it. It is just a static website that provides static information. Rather than using portal, the public can accessed and send a feedback or questions that can be answered by responsible direct seller. Due to that reason, the researcher conducting this research and produce a prototype of direct selling portal that can be accessed by public.